A place and role of an ontology in using a base of experience in designing the software intensive systems. Issue 1 (18th April 2016) - Sosnin, Petr
Abstract : Purpose: Nowadays, experience bases are widely used by project companies in designing software-intensive systems (SISs). The efficiency of such informational sources is defined by the "nature" of modeled experience units and approaches that apply to their systematization. This paper aims to increase the efficiency of designing the SISs by the use of an ontological support for interactions with an accessible experience, models of which are understood as intellectually processed conditioned reflexes. Design/methodology/approach: Both of the base of experience (BE) and ontological support in interactions with its units are oriented on precedents built in accordance with the offered normative schema when the occupational work is fulfilled by a team of designers. In creating the BE and the ontology as part of the BE, the team should use a reflection of an operational space of solved tasks on a specialized semantic memory intended for simulating the applied reasoning of the question-answer type. Findings: If the occupational space of designing is reflected on the semantic memory with a programmable shell, then this environment can be adjusted on simulating the intellectual mechanisms flown in a human consciousness when designers ontologically interact with the BE and tasks being solved. The use of simulating the process in consciousness in accordance with their nature facilitates increasing the efficiency of designing the SIS. Research limitations/implications: An orientation on a precedent model as a basic type of experience unit and an ontological approach to their systematization are defined by the specificity of the study described in this paper. Models of precedents are constructed in accordance with the normative schema when the occupational work is fulfilled by a team of designers. Practical implications: Investigated and developed means of ontological support are oriented on effective designing of the SISs with the use of the toolkit Working In Questions and Answers (WIQA) by the team of designers. The achieved effects are aimed at increasing the level of success in collaborative designing of SISs. Social implications: Offered solutions are applicable in designing the systems which supported different relations of a human with artificial and natural environment. They facilitate the naturalness in interactions of a human with computerized world. Originality/value: An orientation on the precedent model as a basic type of experience unit and the ontological approach to their systematization are defined by the specificity of the study described in this paper. The novelty of this approach is defined by the framework for the precedent model, understood as the intellectually processed conditioned reflex, in which a reflection on the semantic memory (of the question-answer type) is programmable in a conceptually algorithmic language. The ontological support is implemented in the environment of programming.